Therapeutic potential of regulatory cytokines that target B cells - Fujio, Keishi (Int Immunol, 2016)
Autoreactive B cells play a crucial role in the pathogenesis of autoimmune diseases by producing auto-antibodies and presenting antigens. Regulatory cytokines that simultaneously suppress multiple pathways have the potential to control autoreactive B cells. The generally inhibitory cytokine IL-10 may have a stimulatory effect on human B-cell survival and antibody production. TGF-β family cytokines can decrease or increase antibody production and can suppress B-cell proliferation and differentiation. In contrast to TGF-β1, which induces extensive fibrosis, TGF-β3 and bone morphogenetic protein 6 (BMP-6)/BMP-7 induce non-scarring wound healing and counteract tissue fibrosis. Therefore, TGF-β3 and BMP-6/BMP-7 may be clinically applicable as therapeutic cytokines that target B cells. Recent progress in protein engineering may enable us to generate novel biologic therapies based on TGF-β family cytokines.